IMPLEMENTASI ALGORITMA FUZZY PADA SISTEM KONTROL AQUAPONIK PADI - Kahfi, Ibnu; Fauzi, Rizana; Subito, Mery; Sollu, Tan Suryani; Alamsyah, Alamsyah (Foristek, 2024)
Aquaponics is an agricultural system that combines fish and plant cultivation in one closed system. In an aquaponics system, the water used for fish cultivation is also used to irrigate plants with rice aquaponics as one example. However, monitoring and controlling aquaponic systems is still done manually, which has many shortcomings, including requiring a relatively long time and accuracy that is not guaranteed, especially in large-scale aquaponics management. Implementing the fuzzy algorithm in the rice aquaponics control system aims to make it easier for farmers to monitor the condition of the rice and control the water change system in the pond in real time via the Blynk application on their smartphone. This system combines ESP-32 technology, fuzzy algorithms, and the Internet of Things (IoT) to monitor and control the rice aquaponics system. The results of data collection from the implementation of the fuzzy algorithm in the rice aquaponics control system show that the tool functions well. This tool can monitor the condition of rice and control the water change system in the pond in real time using the Blynk application. The level of accuracy of implementing the fuzzy algorithm for monitoring rice conditions was 99.61% and the accuracy of implementing the fuzzy algorithm for pump control of the water change system was 98.95%.